The effect of celebrity endorsement on consumer decisions using the Ruangguru application - Dwi Nuryanti; Azizah Fauziyah; Ismail Yufus (Institute of Computer Science (IOCS), 2023)
Celebrities in the modern era fulfill a powerful role in various marketing communications activities. Indonesia is one country that has many celebrities who take advantage of this condition, have a role as communicators in sales promotions. Currently, the trend in Indonesia, the use of social media spreads instantly which reflects the image, idea, reason or product. In general, consumer perceptions and intentions to buy a product are related to its characteristics or to imitate the person who uses it. The trend of using celebrities in sales promotions is massive and expanding to all sectors, including the education sector. One brand that utilizes the role of celebrities in its marketing is Ruangguru. A Brand engaged in the education sector. This study aims to determine the effect of celebrity endorsers on consumer decisions using the Ruangguru application. The type of research data n is quantitative which comes from filling out the questionnaire. Measurement of data in this study using a Likert scale. The population in this study were students of SMA Negeri 15 Jakarta. The sample used as many as 86 respondents. The sampling technique in this study used sampling with a non-probability sampling technique. The method used in this study is the purposive sampling method. The test instrument used in this study used the Validity Test and Reliability Test. The data analysis technique used in this research simple linear regression analysis. The hypothesis in this study is there is no positive influence between celebrity endorsers and purchasing decisions. The results showed that celebrity endorsers influenced students' decisions to use the Ruangguru application by 59%.